Home security based on internet application - Ruzzaida, Kamaruldzaman (2009)
Internet is the most popular communication system being used in this globalisation world. This security system was developed based on internet application. Visual studio 2005 is used to create interface for user to communicate with the system. Magnetic sensor is used to detect whether there are intruder entered the house during ON mode of the system. The use of PIC16F877A is to control and link the main component such as sensor, serial port and Graphical User Interface. This GUI can communicate with user by using internet. As long as there are internet connection surround, this system can be access. Hardware and GUI part communicate through the serial port of a PC. A serial connector called DB9 is used to exchange data between PC and PIC16F877A. This system required user to enter username and password for safety reason. Liquid crystal display ( LCD ) is used to display the result of the systems.